2005
DOI: 10.1136/jmg.2004.029173
|View full text |Cite
|
Sign up to set email alerts
|

Ehlers-Danlos syndrome and periventricular nodular heterotopia in a Spanish family with a single FLNA mutation

Abstract: Methods: A clinical and molecular study was undertaken in the three affected women. Clinical histories, physical and neurological examinations, brain magnetic resonance imaging studies, and skin biopsies were done. Genetic analysis of the FLNA gene was undertaken by direct sequencing and restriction fragment length polymorphism analysis. Results: Mutation analysis of the FLNA gene resulted in the identification of a novel mutation in exon 3 (c.383CRT) segregating with the combination of both syndromes. This mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…3 Over the past few years, several new forms have been clinically and molecularly delineated, including dermatan 4-O-sulfotransferase 1 deficient-EDS, spondylocheiro dysplastic EDS (caused by mutation of the SLC39A13 gene) and the X-linked periventricular heterotopia variant (PH-EDS), caused by mutations in Filamin A. [4][5][6][7] In fact, the existence of EDS type VIII, as a specific EDS form associated with periodontal disease and having a distinct underlying genetic basis, is still debated in the literature. This is based in part on the reported association of gingivitis (and sometimes subsequent periodontitis) with other subtypes of EDS (eg, the classic, hypermobile and vascular forms), 3,8 arguing that gingival involvement may be considered a nonspecific consequence of various heritable connective tissue disorders.…”
Section: Discussionmentioning
confidence: 99%
“…3 Over the past few years, several new forms have been clinically and molecularly delineated, including dermatan 4-O-sulfotransferase 1 deficient-EDS, spondylocheiro dysplastic EDS (caused by mutation of the SLC39A13 gene) and the X-linked periventricular heterotopia variant (PH-EDS), caused by mutations in Filamin A. [4][5][6][7] In fact, the existence of EDS type VIII, as a specific EDS form associated with periodontal disease and having a distinct underlying genetic basis, is still debated in the literature. This is based in part on the reported association of gingivitis (and sometimes subsequent periodontitis) with other subtypes of EDS (eg, the classic, hypermobile and vascular forms), 3,8 arguing that gingival involvement may be considered a nonspecific consequence of various heritable connective tissue disorders.…”
Section: Discussionmentioning
confidence: 99%
“…19 The recognition of progressive vascular defects associated with XL-PH raises the potential for rupture and sudden death in this condition. Descriptions of cohorts of patients with XL-PH do not report such clinical incidents suggesting that this is not a common complication of the disorder, 4,5,7,8,11,12,15,16 although data have not been prospectively sought to answer this specific question. The precise incidence of XL-PH and aortic dilatation is unknown, complicating this uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…3 Two previous reports linked XL-PH to a connective tissue disorder characterized by joint hypermobility, cutaneous anomalies and aortic aneurysms (Ehlers-Danlos syndrome (EDS)-PH; OMIM #300537), and reported three sporadic and one familial case of the association. 4,5 The clinical manifestations of this syndrome are poorly defined since the detailed descriptions of some reported cases are not available. It is also unclear if the four FLNA mutations that underlie EDS-PH are functionally different from those that cause generic XL-PH.…”
Section: Introductionmentioning
confidence: 99%
“…Two genes were identified that can cause PNH. Mutations in the Xlinked gene filamin-A (FLNA) result in PNH, but also can give rise to aortic aneurysms, blood abnormalities, and the heritable connective tissue disorder called Ehlers-Danlos syndrome [Sheen et al, 2001[Sheen et al, , 2005Gomez-Garre et al, 2006]. In addition, mutations in FLNA also can give rise to OPD/Frontometaphyseal spectrum of conditions [Robertson et al, 2003;Zenker et al, 2004;Hehr et al, 2005].…”
Section: Introductionmentioning
confidence: 97%